2019
DOI: 10.1186/s40792-019-0711-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transhiatal suture closure for spontaneous esophageal rupture: a case report

Abstract: BackgroundSpontaneous esophageal rupture is a rare but serious disease with high mortality. Conservative treatment and endoscopic therapy have been reported, but surgical treatment is still a basic modality of therapy. In addition to thoracotomy, recent studies have reported treatment with thoracoscopic surgery and laparoscopic transhiatal repair. In this study, we report a patient who underwent laparoscopic transhiatal suture closure for spontaneous esophageal rupture with favorable postoperative course. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Two patients followed a good postoperative course, but 1 patient subsequently succumbed to multi-organ failure. Since then, Kimberley et al [ 6 ], Yeo et al [ 7 ], Hayakawa et al [ 8 ], and Aiolfi et al [ 9 ] have reported a total of 5 cases of Boerhaave's syndrome repaired by only laparoscopic surgery via the transhiatal route. There were no reports of mortality, and good postoperative results were obtained, except for the early case of Landen and El Nakadi [ 5 ] (Table 1 ) [ 6 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients followed a good postoperative course, but 1 patient subsequently succumbed to multi-organ failure. Since then, Kimberley et al [ 6 ], Yeo et al [ 7 ], Hayakawa et al [ 8 ], and Aiolfi et al [ 9 ] have reported a total of 5 cases of Boerhaave's syndrome repaired by only laparoscopic surgery via the transhiatal route. There were no reports of mortality, and good postoperative results were obtained, except for the early case of Landen and El Nakadi [ 5 ] (Table 1 ) [ 6 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, Kimberley et al [ 6 ], Yeo et al [ 7 ], Hayakawa et al [ 8 ], and Aiolfi et al [ 9 ] have reported a total of 5 cases of Boerhaave's syndrome repaired by only laparoscopic surgery via the transhiatal route. There were no reports of mortality, and good postoperative results were obtained, except for the early case of Landen and El Nakadi [ 5 ] (Table 1 ) [ 6 , 7 , 8 , 9 ]. When performing the laparoscopic esophageal repair via the transhiatal route, avoiding penetrating the pleura is vital as it is important not to spread the inflammation in the thoracic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Which is the best way to approach BS is still a matter of debate: actual guidelines for thoracic esophageal perforation suggest an individualized approach to primary repair the tear, while for what concern specifically esophageal spontaneous rupture, most of the available studies considered the thoracotomy/thoracoscopic approach as the way of choice [9,[17][18][19][20][21]. Anyway, there is not any specific guidelines for BS: some case reports suggest that laparoscopy may be just as safe and effective [12,13]; lastly, some authors also reported conservative or endoscopic treatment: nevertheless, these are just a few studies involving patients with less severe clinical picture, so further researches are needed to better understand their feasibility in more challenging conditions [5,7]. In this case series, we present our 5 years' experience: in all patients, we choose to approach laparoscopically the esophageal tear; when necessary, afterwards we performed a thoracic lavage through left thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the type of surgical approach, thoracotomy is the most frequently chosen approach even if in literature there are several studies reporting transhiatal management as much as safe [11][12][13]. In our department, transabdominal approach is routinely adopted to treat BS.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Open surgical closure with suturing by thoracotomy or laparotomy is the gold standard in the treatment of esophageal perforation, although recent reports describe using laparoscopy and thoracoscopy. 3 , 4 Esophageal stents and polyglycolic acid sheets in upper gastrointestinal endoscopy are some of the treatments reported to have been attempted for patients with perforations because there are no established treatments. 5 , 6 Patients with esophageal perforation frequently experience Boerhaave syndrome (BS), which is an acute-onset condition with vomiting symptoms as the trigger; these patients frequently present with chest pain as the primary complaint.…”
Section: Introductionmentioning
confidence: 99%